Missing Insight Into T and B Cell Responses in Dermatitis Herpetiformis - Kemppainen, Esko; Salmi, Teea; Lindfors, Katri (Frontiers in Immunology, 2021)
Dermatitis herpetiformis is a cutaneous form of celiac disease manifesting as an itching rash typically on the elbows, knees and buttocks. It is driven by the ingestion of gluten-containing cereals and characterized by granular deposits of immunoglobulin A in the papillary dermis. These antibodies target transglutaminase (TG) 3 and in the majority of patients they are also found in circulation. The circulating antibodies disappear, and skin symptoms generally resolve as a result of gluten-free diet but the cutaneous anti-TG3 IgA deposits may persist for several years. In dermatitis herpetiformis, plasma cells secreting antibodies against TG3 are located in the intestinal mucosa similarly to those producing TG2 antibodies characteristic for celiac disease. In fact, both TG2- and TG3-specific plasma cells and gluten responsive T cells are found in dermatitis herpetiformis patients but the interplay between these cell populations is unknown. The small bowel mucosal damage in celiac disease is believed to be mediated by co-operation of cytotoxic intraepithelial T cells and the inflammatory milieu contributed by gluten-reactive CD4+ T cells whereas the skin lesions in dermatitis herpetiformis appear to be devoid of gluten reactive T cells. Thus, how celiac disease-type intestinal T and B cell responses develop into an autoimmune condition affecting the skin is still incompletely understood. Finally, the skin and small bowel lesions may reappear upon reintroduction of gluten in patients treated with gluten-free diet but virtually nothing is known about the long-lived B cell and memory T cell populations activating in response to dietary gluten in dermatitis herpetiformis.